2018
DOI: 10.1038/s41393-018-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance of people with traumatic spinal cord injury: a cross-sectional study comparing people with subacute and chronic injuries

Abstract: In participants with SCI, cognitive dysfunctions are present in the subacute stage and worsen over time. From a clinical point of view, we confirmed the presence of cognitive dysfunction that may interfere with the first stage of rehabilitation which is the most intense and important. Moreover, cognitive dysfunction may be important beyond the end of the first stage of rehabilitation as it can affect an individual's quality of life and possible integration to society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 27 publications
1
30
1
1
Order By: Relevance
“…Routine cognitive assessments should be encouraged in this population considering that cognitive dysfunctions, which are present in the subacute setting, worsen over time (ie, in chronic stages), and have significant implications for individuals aging with SCI. The majority of neuropsychological tests assessed in this present study displayed good‐to‐excellent reliability when administered to individuals with chronic SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Routine cognitive assessments should be encouraged in this population considering that cognitive dysfunctions, which are present in the subacute setting, worsen over time (ie, in chronic stages), and have significant implications for individuals aging with SCI. The majority of neuropsychological tests assessed in this present study displayed good‐to‐excellent reliability when administered to individuals with chronic SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population poor cognitive function is associated with unemployment and lower work performance, reduced health literacy [5], depression [6], and increased mortality [7]. Impaired cognition presents in the sub-acute phase post-SCI, which may impede functional rehabilitation, and worsens over time [8]. Reduced cognitive performance has been demonstrated in chronically-injured SCI individuals compared to age-matched non-injured controls [9].…”
Section: Introductionmentioning
confidence: 99%
“…Second, heterogeneity among participants has limited the predictive validity of the MCI diagnosis [11]. Individuals with SCI display different trajectories of MCI, varying from remission [21,24], stabilization [25], to worsening [13], possibly as a result of distinct underlying 'causes' that can be identified as differentiable etiological subtypes [26,27]. It has been suggested that the predictive validity of a MCI diagnosis improves by subtyping [28], but as far as known, there are no SCI studies that have applied subtyping to clarify such distinctions.…”
Section: Introductionmentioning
confidence: 99%
“…TBI significantly increases an individual's risk of MCI after SCI [11,13,[18][19][20][21][22][23][24][25][26]. Mild and mild-complicated forms of TBI interfere less with cognition than do severe forms of TBI; however, mild-complicated and moderate TBI appear undifferentiable in terms of their influence on cognition [35,55,56].…”
Section: Introductionmentioning
confidence: 99%